The role of perfectionism in the dual pathway model of disordered eating - Amion, Erickson Alibutud (Animo Repository, 2024)
This research aims to test the Dual Pathway Model (DPM) of disordered eating developed by Stice (2001) in a non-Western culture. It also seeks to extend the model by assessing the possible impact of perfectionism, which has been associated with disordered eating behaviors. Responses from 181 female participants were analyzed. Constructs that were inherently part of the model and perfectionism were assessed at baseline with negative affect, dietary restraint, and disordered eating were reevaluated at a 1-month follow-up to gauge the consistency and stability of the response. The data was analyzed using PLS-SEM. Both the measurement model and the structural model were assessed. Results indicate robust support for the DPM of disordered eating, which remains consistent in T1 and T2. It also shows that perfectionism significantly predicted pressure to be thin and ideal internalization but not body dissatisfaction. Mediation analysis shows that perfectionism demonstrates an indirect effect on disordered eating through pressure to be thin, body dissatisfaction, negative affect, and dietary restraint.